Korean experience of process safety management (PSM) regulation for chemical industry. (July 2016) - Kwon, Hyuck-myun; Lee, Chang-jin; Seo, Donghyun; Moon, Il
Abstract: From the 1960s, Korean industries have been encouraged by the government to nurture heavy and chemical industry and to modernize the economics and industrial structures. The development of chemical industry particularly became the turning point in industrial development, and played a major role in the construction of a new industrialized country. However, the process systems in the chemical industry have become more complex and larger, and the inventories of dangerous chemicals that are produced or consumed have continuously increased. Therefore, the hazards from potential accidents such as fire and explosion or release of toxic chemicals have also increased. In fact, from the end of 1980s to the beginning of 1990s in Korea, a number of major industrial accidents such as ABS extruder explosion, TDI release and dryer explosion, etc. Occurred and caused many fatalities. As the chemical companies recognized the importance of preventing major hazards, PSM system, the prevention of major industrial accidents, was introduced in January 1995 by amending Industrial Safety and Health Act, and it has been enforced from January 1, 1996. According to the law, the business owner of a workplace with hazardous or dangerous equipment shall submit a process safety report to the Government to prevent any accidents, which could inflict an immediate damage on workers or on areas in the vicinity of the workplaces. As a result of PSM implementation for 19 years, chemical accident prevention system has been stabilized and various kinds of effectiveness and desirable customer satisfaction have been made. Highlights: From the 1960s, Korean industries have been encouraged to chemical industry. The hazards from potential accidents have also increased. As the chemical companies recognized the importance of preventing major hazards. PSM system is the prevention of major industrial accidents. PSM implementation for 19 years, chemical accident prevention system has been stabilized.